Fragmentation and fish passage: can fishways mitigate discontinuities in Great Plains fish communities? - Pennock, Casey A. (Kansas State University, 2016)
Fishways are a common tool for mitigating the effects of habitat fragmentation on fish communities, but their utility in low-gradient, sand-bed rivers of the Great Plains is not well studied. The Lincoln Street Fishway on the Arkansas River became operational in 2015 and was built specifically to pass small-bodied threatened fishes. We used a combination of surveys up-and downstream of the barrier and tagging experiments to test the ability of fishes to move into and through the fishway. Differences in fish community structure up- and downstream of the dam were more pronounced prior to the construction and operation of the fishway. In particular, Emerald Shiner Notropis atherinoides was absent from collections upstream of the dam before fishway construction, but commonly collected upstream in 2015 and 2016 surveys. Surveys within the fishway structure revealed 29 species, or 74% of the total species captured during our study were using the fishway. To further quantify fishway passage, we used a VIE experiment to assess if fish marked downstream of the fishway moved into or upstream of the fishway. Although we did not recapture marked fish upstream of the fishway, some marked individuals moved into the fishway. Finally, we conducted a PIT tag experiment to evaluate short distance movements within the fishway for three species of small-bodied minnow and were able to document upstream movement across a gradient of flows through the fishway. Results from our study illustrate the potential for fishways to mitigate the effects of habitat fragmentation on small-bodied fishes in sand-bed rivers.
Keywords: Arkansas River; Kansas; Fishway; Fish ecology; Dams; Community structure